COMPARISON OF OVULATION INDUCTION LETROZOLE AND CLOMIPHENE CITRATE IN SUBFERTILE WOMEN WITH POLYCYSTIC OVARIAN SYNDROME: Ovulation Induction Letrozole and Clomiphene Citrate - Shafiq, Amna; Akbar, Rabiya; Urooj, Uzma; Zohra, Sadaf; Afzal, Shazia; Tanveer, Madiha (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare the ovulation induction of letrozole and clomiphene citrate in sub-fertile women with polycystic ovarian syndrome. Study Design: Quasi experimental study. Place and Duration of Study: Combined Military Hospital Rawalpindi, from Jun 2018 to Aug 2019. Methodology: A total of 116 married sub-fertile women with polycystic ovarian syndrome, 16-40 years of age were included. Patients with previous surgery related to genital tract, hypothyroidism and chronic renal failure were excluded. Letrozole 5.0mg daily from Day 5-9 of menstruation was prescribed to group A women and clomiphene citrate 100 mg daily from Day 5-9 of menses was given to group B women. Results: In group A and in group B, mean age was 29.78 ± 4.71 years and 29.95 ± 4.22 years respectively. Most of the patients 59 (50.86%) were between 18-30 years of age. Mean duration since marriage was 4.23 ± 1.42 years. Mean body mass index was 29.71 ± 2.65 kg/m2. Frequency of ovulation of clomiphene citrate and letrozole in sub-fertile women with polycystic ovaries was 28 (42.28%) versus 42 (72.41%) respectively (p-value=0.008). Conclusion: This study concluded that ovulation induction of letrozole is better than clomiphene citrate in sub-fertile women with polycystic ovarian syndrome.